Glyoxylic Acid versus Ethyl Glyoxylate for the Aqueous Enantioselective Synthesis of α-Hydroxy-γ-Keto Acids and Esters by the N-Tosyl-(Sa)-binam-l-prolinamide-Organocatalyzed Aldol Reaction - Moles, Fernando J. N.; Guillena, Gabriela; Nájera, Carmen; Gómez-Bengoa, Enrique (Synthesis, 2015)
N-Tosyl-(Sa)-binam-l-prolinamide is an efficient catalyst for the aqueous aldol reaction between ketones and glyoxylic acid, as the monohydrate or as an aqueous solution, or a 50% toluene solution of ethyl glyoxylate. These reactions led to the formation of chiral α-hydroxy-γ-keto carboxylic acids and esters in high levels of diastereo- and enantioselectivities (up to 97% ee), providing mainly anti aldol products. Only cyclopentanone and cyclohexane-1,4-dione afforded an almost 1:1 mixture of the syn/anti-diastereoisomers; however, the reaction between 4-phenylcyclohexanone and ethyl glyoxylate gave the corresponding syn,syn-product as the major diastereoisomer.
Keywords: aldol reaction; organocatalysis; glyoxylic acid; prolinamide; water